Pneumocystis Jirovecii Pneumonia Associated with Diffuse Alveolar Hemorrhage in a Renal Transplant Patient. Case Report; [Neumonía por Pneumocystis Jirovecii Asociada a Hemorragia Alveolar Difusa en Un Paciente Con Trasplante Renal] - Zamora-Vargas, F; Raijmakers-Hidalgo, M (Sociedad Chilena de Infectologia, 2023)
Pneumocystis jirovecii pneumonia is an opportunistic fungal infection, described mainly in HIV patients, however, after the introduction of ART, its presentation has increased in patients with non-HIV immu-nosuppression, such as hematological cancers, solid or hematopoietic stem cell transplantation. We report the case of a 17-year-old male, kidney transplant patient, with prolonged immunosuppression with corticoesteroids, with history of cough, dyspnea, and fever. Chest CT evidences centrilobular pulmonary micronodules with ground glass. BAL was performed compatible with diffuse alveolar hemorrhage, with positive PCR for P. jirovecii. Other infections and autoimmune disease were ruled out. He received treatment with cotrimoxazole with clinical improvement of the patient, and follow up chest CT at the end of treatment showed decrease of pulmonary infiltrates. Although the most frequent causes of DAH are autoimmune etiologies such as rheumatic diseases or vasculitis, it is a priority to rule out infectious causes, including P. jirovecii, since targeted treatment could have a significant impact on mortality outcomes in this group of patients. © 2023, Sociedad Chilena de Infectologia. All rights reserved.